On lookahead equilibria in congestion games. (6th May 2015) - BILÒ, VITTORIO; FANELLI, ANGELO; MOSCARDELLI, LUCA
Abstract : We investigate the issues of existence and efficiency of lookahead equilibria in congestion games. Lookahead equilibria, whose study has been initiated by Mirrokni et al. (2012 ), correspond to the natural extension of pure Nash equilibria in which the players, when making use of global information in order to predict subsequent reactions of the other ones, have computationally limited capabilities.